Synthesis and controlled release characterization of zincaluminium- herbicide hybrid nanomaterials / Sheikh Ahmad Izaddin Sheikh Ahmad Ghazali - Sheikh Ahmad Ghazali, Sheikh Ahmad Izaddin (Institute of Graduate Studies, UiTM, 2016)
In the modern agriculture, various agrochemicals such as pesticides, herbicides, and plant growth regulators are widely used for effective pest management and ensuring optimum crop yield. Most herbicide formulations deliver the bulk of the active agents that can be readily released to the environment. This phenomenon leads to pesticide residues in the food chain, and this, in turn, has adverse effects in humans including carcinogenic, mutagenic, and teratogenic effects. As a solution for this, we developed a controlled release agrochemical in which the herbicide is embedded into a matrix that can be released in a controlled condition manner. This study aimed at the synthesis of a new controlled release of herbicides, namely 2-methyl-4-chlorophenoxy acetates (MCPA), 2,4,5-trichlorophenoxybutyrate (TBA) and 3,4-dicholorophenoxy acetates(3,4D) through intercalation of the herbicides into zinc-aluminiumlayered double hydroxide by self-assembly and anion-exchange method. The release of herbicides into various aqueous media and the kinetic profile were also studied after the successful intercalation of the herbicides at their optimum condition. In this study, a phase pure, well-ordered nanocomposite was successfully synthesized using both self-assembly and anion-exchange method…